Tren Inovasi Bisnis Syariah: Menggali Potensi Pasar dan Etika Berbisnis - Hafiz, Muhammad; Mairiza, Diany; Meilany, Merry (Multidisciplinary Journal of Religion and Social Sciences, 2024)
This study aims to identify innovation trends in sharia business, explore the potential of the sharia market, and examine the application of business ethics according to sharia principles. Through a qualitative approach with a literature study method, this study analyzes various sources from scientific journals and relevant articles to provide a comprehensive picture of the development of innovation, market opportunities, and ethical principles in sharia business. The results of the study indicate that digital innovation, especially through sharia fintech, plays an important role in increasing access to sharia financial services and expanding market reach. In addition, the potential for the sharia market is growing rapidly among Muslim and non-Muslim consumers who prioritize halal and ethical products. Sharia business is also considered to have its own appeal because it upholds ethical principles, such as fairness and transparency, which help build consumer trust. Overall, this study concludes that the combination of innovation and ethics is the key to the success and sustainability of sharia business. Businesses that are consistent in implementing these two elements have the potential to develop competitively and sustainably in the global market.